Creativity and Cultural Congruence in Adolescence - Larisa F. Bayanova; Aisylu M. Ganieva (Национальный психологический журнал, 2023)
Background. The study of cultural congruence as a personality trait responsible for the regulation of adolescent behavior in relation to the rules typical for this age is one of the important tasks for developmental psychology. The range of rules despite its diversity has an invariant series. This invariant part of diversity is specific for each age stage. the contradiction between the need to follow generally accepted rules and conditions for the development of creativity associated with atypical and original products of creative activity makes up the problem of studying cultural congruence of creative teenagers. There is a lack of research on the relationship between two diametrically opposed psychological qualities of adolescents: cultural congruence and creativity. The objective of the study is to analyze the correlation between cultural congruence and creativity; as well as to study the influence of divergent thinking on the cultural congruence in adolescents. Sample. The research was conducted in 4 stages between March 2021 and March 2022 and involved 272 adolescents, ages 13 to 16 (М = 14.21; SD = 1.02), (139 male and 133 female). Students of 7th, 8th, and 9th grades at four lyceums in Kazan took part in the study. Methods. The methods included the test of divergent creative thinking (F. Williams, modified by E.E. Tunik, 2003), the questionnaire to diagnose the level of cultural congruence for adolescents (L.F. Bayanova, O.G. Minyaev, 2016), the test to identify creative abilities (H. Zievert, 1998). The study assessed the following parameters: curiosity, imagination, risk-taking, self-discipline, quick-thinking, divergent thinking, cultural сongruence as the ability to control behavior regarding the rules typical of the social situation of development in adolescence. Mathematical data processing was carried out using methods of descriptive statistics, Pearson correlation coefficient (r), Cheddock scale, the one-way analysis of variance (ANOVA). Results. The research of the indicators of divergent thinking, creative characteristics, and cultural congruence of adolescents concludes that of the variety of dichotomous relations, a significant inverse correlation was found between the structural component of cultural congruence, i.e., “safety” and divergent thinking (confidence level is 95% (p ≤ 0.05; r = –12). It provides a partial confirmation of the hypothesis. The final stage of the research included an analysis of variance using the one-factor ANOVA method. Following the results of the analysis, it was found that the influence of divergent thinking on the cultural congruence of adolescents is not significant. Conclusion. The data obtained indicate a weak correlation of the ambivalent factors, i.e., creativity and cultural congruence. The results show an inverse correlation between creativity and the “safety” scale of the method for diagnosing the cultural congruence for adolescents. The revealed ambivalence of the studied indicators distinguishes the nature of correlations, identified previously in the study of behavior regulation and creativity of preschool and primary school children.